2014
DOI: 10.1021/mp4004139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Doxorubicin α-Linolenic Acid Conjugate and Evaluation of Its Antitumor Activity

Abstract: Doxorubicin (DOX) is a broad-spectrum antitumor drug used in the clinic. However, it can cause serious heart toxicity. To increase the therapeutic index of DOX and to attenuate its toxicity toward normal tissues, we conjugated DOX with either α-linolenic acid (LNA) or palmitic acid (PA) by a hydrazone or an amide bond to produce DOX-hyd-LNA, DOX-ami-LNA, DOX-hyd-PA, and DOX-ami-PA. The cytotoxicity of DOX-hyd-LNA on HepG2, MCF-7, and MDA-231 cells was higher compared to that of DOX, DOX-ami-LNA, DOX-hyd-PA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…54 Hydrazone bonds have been successfully used to synthesize pH-sensitive lipid conjugated doxorubicin (Figure 2C). 5557 …”
Section: Chemical Bondsmentioning
confidence: 99%
“…54 Hydrazone bonds have been successfully used to synthesize pH-sensitive lipid conjugated doxorubicin (Figure 2C). 5557 …”
Section: Chemical Bondsmentioning
confidence: 99%
“…At the difference with ester or amide linkages between the phenolic compound and the PUFA part, non hydrolysable bounds have been obtained [38] [18][19]29] (dopamine and analogues) 11 [26,29,67] (vanillyl amine) 14 [17] ( [28] (Farinosone C analogue) 21 [20] (juglone) 22 [23] (shikonin) Dox-hyd-PUFA: 24a Dox-3-ami-PUFA: 24b (doxorubicin) [25,[63][64][65] 23 [27] (podophyllotoxin analogue) DDPT 15 [37] (phloroglucinol) 4'-PUFA:17a [22,37] 3-DHA: 17b (resveratrol) 18 [21] (trimethoxy anilide) 19 [24,66] (diisopropylphenol) 3 5 4' 3 3 2 [34][35] (EGC) 3 [36] (quercetin) 4 [15] (naringin) 5 [10][11][13][14][15] (rutin) 6 [12] (phloridzin) 7 [12] (isoquercitrin) 8 [38] 9 [30] 10 [ linker [39]. Since pH in tumor cells is lower than in healthy tissue, the hydrazone bond, stable at pH 7.4, is rapidly cleaved at lower pH in cancerous cells.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…However, saturated heptadecanoyl analogue reduced metabolic activity of the cell lines more than the unsaturated DOX-hyd-ALA. In parallel, Liang et al [65] studied in vitro (MCF-7, MDA-MB-231, and HepG2) and in vivo (mice) activities of DOX-ALA and DOX-PA (palmitate) either linked through an hydrazone bound (DOX-Hyd-ALA 24a) or by the daunosamine residue (DOX-ami-ALA 24b). In this study, saturated or unsaturated fatty acid on the 3 0 amino group lead to a decrease in antitumor activity compared to DOX and DOX-hyd-ALA. DOX-hyd-ALA showed the highest cytotoxicity, stability in bloodstream, and fastest release of DOX in acidic tumor cells.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that fatty acids exhibit broad spectrum of activity which make them attractive molecules for preparing various biologically active compounds of interest in biomedical fields. In view of these properties, various fatty acids have been combined with therapeutically active compounds to produce novel hybrid molecules anticipating enhanced biological activity 13,14 .…”
Section: Introductionmentioning
confidence: 99%